HUBUNGAN POLA KONSUMSI INHIBITOR DAN ENHANCER ZAT BESI, KEBIASAAN SARAPAN DAN SIKLUS MENSTRUASI DENGAN GEJALA ANEMIA REMAJA PUTRI SMA IT DAARUL RAHMAN III TAHUN 2022 - Ni Luh Eva Laraswati (2022)
Adolescent girls who undergo high school education are included in the category of reproductive age women, which is a group that has a high risk of suffering from anemia. The incidence of anemia in adolescent girls continues to increase every year in Indonesia. Anemia in young women can cause them to be susceptible to infection, easily tired, decreased enthusiasm for learning, to stunted growth. There are several factors that can affect the occurrence of anemia. The purpose of this study was to determine the relationship between consumption patterns of iron inhibitors and enhancers, breakfast habits and menstrual cycles with symptoms of anemia in adolescent girls at SMA IT Daarul Rahman III in 2022. This study was a quantitative research using a cross sectional design. Sampling was done by stratified random sampling, obtained a sample of 77 female respondents aged 15-18 years. Data regarding symptoms of anemia, breakfast habits and menstrual cycle were obtained from filling out a questionnaire. Data on consumption patterns of iron inhibitors and enhancers were obtained through interviews using the Food Frequency Questionnaire (FFQ) sheet. The results of the univariate analysis showed that most of the respondents (58.4%) had no symptoms of anemia. The results of bivariate analysis using the chi-square test showed a relationship between consumption patterns of iron inhibitors (p=0.023) and enhancers (p=0.009), breakfast habits (p=0.013) and menstrual cycle (p=0.011) with symptoms of anemia in adolescent girls at SMA IT Daarul Rahman III. During menstruation, the girls can eat foods rich of iron and its enhancers and avoid consuming foods that contain iron inhibitors.